Impact of biomass burning and non-exhaust vehicle emissions on PM10 levels in a mid-size non-industrial western Iberian city. (15th November 2022) - Pio, Casimiro; Rienda, Ismael Casotti; Nunes, Teresa; Gonçalves, Cátia; Tchepel, Oxana; Pina, Noela K.; Rodrigues, João; Lucarelli, Franco; Alves, Célia A.
Abstract: PM10 aerosol was measured during one semester, simultaneously, at a roadside (RS) and an urban background (UB) location in Coimbra, Portugal. On average, the mass concentrations were 36% higher at the RS, compared to UB. Application of Positive Matrix Factorisation (PMF) and Ionic Mass Balance (IMB) methodologies permitted to source apportion the aerosol mass. During the cold season, biomass burning was a prevalent particulate matter source at both urban locations, contributing with up to 30% of PM10 . At the RS, vehicle non-exhaust emissions (brake, tyre and road dust) doubled exhaust emissions by combustion engines, accounting for 18–19% of PM10 . Unreacted and reacted sea salt was an important fraction of PM10, principally during the warm season, when it composed approximately 25% of the aerosol. Secondary pollution by ammonium salts and carbonaceous matter was important across the seasons, especially at the UB location, where they dominated the particulate mass. Highlights: PMF and IMB were used to apportion the PM10 urban aerosol at a roadside and an urban background sites, in Portugal. Biomass burning was a major source of the urban aerosol, during winter. IMB permitted the separated estimation of road traffic exhaust, road dust, break wear and tyre wear inputs to measured PM10 . At roadside, non-exhaust emissions were twice by comparison with the engine exhaust source. The three road traffic non-exhaust sources contribute equally to the PM10 loading.